REKAYASA MODEL PENGUATAN KESIAPAN KERJA LULUSAN PENDIDIKAN VOKASI (Studi pada SMK di Kota Semarang) - Rauly Sijabat (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
The study of job readiness has been widely researched but is still an interesting topic given the empirical phenomenon which indicates the low level of work readiness. In addition, the findings from the studies that have been conducted on explanatory variables of work readiness are also not conclusive. Departing from this phenomenon, the study again developed a research model that "mated" the empirical and theoretical aspects that could explain the variable work readiness. Empirical testing on the work readiness research model was conducted on vocational education graduates in Semarang who became the object of research. To the object of the study, interviews were conducted using questionnaires to be further analyzed by Structural Equation Modeling (SEM) as an analytical technique approach. Empirical testing results in the research model and the influence of research variables indicate that the research model is the right model to describe the estimated population. The results of testing the influence between variables indicate that graduate competencies are built through training and industrial work practices, the competencies that are built will create locus of control and self efficacy which ultimately strengthens vocational education graduates' job readiness in Semarang.